The environmental contamination in the water-bearing to Ecuador. - Guanoquiza Tello, Lucas (2019)
Ecuador is a rich country in hydric resources. The man's interaction with the biosphere provokes problems: Contamination of the ground, air and water; And issues: Hunger and losses of flora and wildlife. These questions belong to ecology and to the bioethics. In Latin America, the recognition of the water like a human fundamental right and like subject of rights within the frame of the rights of the nature at the Ecuadorian nation, the hydric certainty at the territories constitutes an indispensable step for pre-preventive, that you guarantee the cash enjoy and exercise of the rights to a worthy life, health, nutrition, house, culture, sound environment and the permanence of the natural cycles of the water like a good from the originating towns. The analysis of water has multiple analyses in bulk, quality and allocation of resources hydric, in the interpretation so that it happens with the water in the Ecuador. One of the aspects considered still with weakness is the referred to quality, affected for activities and contaminating processes that they present an absence of policies and state-owned obvious and effective actions like a complex social, cost-reducing and environmental phenomenon, that it constitutes one of the more serious obstacles for the good living. Needy of processes of environmental formation from the bioethics.